2023
DOI: 10.3390/genes14040929
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genomes of Gynostemma Reveal the Phylogenetic Relationships of Species within the Genus

Abstract: Gynostemma is an important medicinal and food plant of the Cucurbitaceae family. The phylogenetic position of the genus Gynostemma in the Cucurbitaceae family has been determined by morphology and phylogenetics, but the evolutionary relationships within the genus Gynostemma remain to be explored. The chloroplast genomes of seven species of the genus Gynostemma were sequenced and annotated, of which the genomes of Gynostemma simplicifolium, Gynostemma guangxiense and Gynostemma laxum were sequenced and annotate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The arrangement and recombination of the cp genome may be significantly influenced by the regions and the numbers of the repeat sequences [61]. The long repeat sequence analysis revealed that palindromic and forward repeats were the most common repeats in E. cymosa and E. obtusifolia (Figure 5), which is consistent with other angiosperm cp genome analyses [62][63][64][65][66]. The SSRs analysis showed that the cp genomes of E. cymosa and E. obtusifolia comprised 141 SSRs and 139 SSRs, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…The arrangement and recombination of the cp genome may be significantly influenced by the regions and the numbers of the repeat sequences [61]. The long repeat sequence analysis revealed that palindromic and forward repeats were the most common repeats in E. cymosa and E. obtusifolia (Figure 5), which is consistent with other angiosperm cp genome analyses [62][63][64][65][66]. The SSRs analysis showed that the cp genomes of E. cymosa and E. obtusifolia comprised 141 SSRs and 139 SSRs, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…The number and regions of repeat sequences might be the reason for the recombination and arrangement events in the chloroplast genome [71]. The palindromic and forward repeats are the dominant types of repeats in the angiosperm plastomes [72][73][74]. The SSRs analysis revealed that both genomes contained 155 microsatellites (Table 2).…”
Section: Discussionmentioning
confidence: 99%